The Role of Physiotherapy in Long COVID Management: A South African Perspective - Kout, Naeema AR Hussein El; Damons, Natalie Benjamin (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Over 4 million people in South Africa have been infected by COVID-19 with many individuals presenting with long COVID. The multiple complications associated with long COVID include neuromuscular skeletal, cardiopulmonary, mental health, gastrointestinal and dermatological complications. Physiotherapy plays an integral role in the management of these complications. There are multiple resources stipulating physiotherapy best practices in managing people living with long COVID. This evidence statement provides a snapshot into evidence-based physiotherapy techniques to best address the multiple complications associated with long COVID. Objectives: To summarise the best evidence of physiotherapy practices in the management of individuals with long COVID. Method: This evidence statement was completed using the steps outlined by the EBSCO evidence-based methodology. Sixty-one articles were sourced and analyzed for inclusion in this statement. Results and discussion: Physiotherapy improves outcomes in people living with long COVID. This includes better lung volumes, improved breathing patterns and improved oxygenation levels. People living with long COVID have also reported improved cardiovascular endurance, better mobility, and muscle strength as well as improved overall quality of life through rehabilitation interventions. Other studies have shown decreased shortness of breath and improved mental health with rehabilitation interventions. Conclusion: A holistic approach to physiotherapy plays an integral role in the management of people living with long COVID. This evidence statement supports clinical practice and informs future research when determining which physiotherapy approach is best suited to manage individuals with long COVID. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 286-293